Developing a sustainable model of rural cancer care: The Western Australian Cancer Network project - McConigley, Ruth; Platt, V.; Holloway, Kristi; Smith, Jodi (Blackwell Publishing, 2011)
Problem: Cancer-related mortality is higher in rural areas than in urban centres. One of the contributing factors is limited access to treatment options in rural areas. Design: An evaluation of the effectiveness of the Western Australian Cancer Network (CanNET WA) pilot project was undertaken using qualitative methods and document analysis. Setting: CanNET WA was established in the Great Southern region of Western Australia. Key measures for improvement: Three measures were assessed: impact of the CanNET WA on consumers, care providers and changes to systems and processes. Strategies for change: CanNET WA comprised a number of initiatives that together led to an improvement in cancer care. These included a multidisciplinary cancer team, improved access to visiting medical specialists, formal links with tertiary cancer centres, increased primary health involvement in cancer care and increased education regarding cancer care for local health care providers. Effects of change: Changes in the three key outcome measures were reported. Consumers had greater choice of treatment options and had more involvement in decision making. Health professionals reported improvements in care coordination and in peer support related to the new multidisciplinary cancer care team, and improved links with tertiary cancer centres in Perth. Systemic changes included mapping of referral pathways and tumour-specific care pathways. Lessons learnt: CanNET WA has demonstrated the need for coordinated cancer care for rural people that offers care locally whenever possible. The success of the project paved the way for the rollout of the CanNET WA concept into other regional areas of Western Australia.